Cardioprotective effects of hUCMSCs-Exosi-EGR1 MN patch in MI/RI by modulating oxidative stress and mitophagy - Chen Huang; Xun Zhang; Shi-Xiong Wu; Qing Chang; Zhi-Kun Zheng; Jing Xu (Materials Today Bio)
In an effort to address the detrimental effects of myocardial ischemia/reperfusion injury (MI/RI), this study introduces a novel therapeutic strategy that involves a microneedle (MN) patch loaded with exosomes derived from human umbilical cord mesenchymal stem cells (hUCMSCs) and carrying small interfering RNA (siRNA) targeting early growth response-1 (EGR1). By delivering hUCMSCs-derived exosomes containing EGR1 siRNA (hUCMSCs-Exosi-EGR1), the MN patch demonstrated promising cardioprotective effects in both in vitro and in vivo models of MI/RI. The results highlighted the efficacy of Exosi-EGR1 in enhancing cardiomyocyte viability, attenuating oxidative stress levels, and fostering mitophagy regulation. Moreover, the Exosi-EGR1 MN patch exhibited excellent mechanical properties and sustained drug release characteristics when embedded in a Gelatin methacryloyl (GelMA) matrix. Noteworthy outcomes from in vivo experiments included significant improvements in cardiac function, reduced cardiac fibrosis, and decreased apoptosis rates in MI/RI mice, emphasizing the potential therapeutic value of the Exosi-EGR1 MN patch in mitigating MI/RI through modulation of oxidative stress and mitophagy mechanisms.